Centro de interpretación de la cultura afrodescendiente del cantón Catamayo Provincia de Loja - Quizhpe Vire, Sara Jimena (2017)
Tourism, during these last years, has been experiencing changes, not only with the increase of the economies in different countries, but also as a dynamic community development; the importance of this activity lies in the human needs to have unique life experiences and to interact with other cultures, by simple curiosity or by the fact of educate and identify themselves. The province of Loja has native cultures, is full of cultural richness and traditions, which keeps in its corners multiple possibilities of knowledge, recreation and experiences, which contains many enigmas that enrich the spirit, here is preserved in an authentic way all the cultural richness, of every single canton that form this province. The canton of Catamayo has a cultural richness as approximately 500 years ago the Afro descendant culture settled down who brought their world view, ideologies, customs and traditions becoming part of the history, identity and culture of this canton, however, has not been properly valued and exploited, for this reason it was important to develop the research work entitled: “INTERPRETATION CENTRE OF AFRODESCENDANT CULTURE OF CANTON CATAMAYO PROVINCE OF LOJA” with the purpose that visitors appreciate the importance of cultural heritage, also the interpretation educate the tourists about the community, improve their experiences, an interpretation centre is considered as a place where it can be appreciated in a simple way and the brief meaning of cultural heritage, allowing to increase the touristic activity in the canton. The present research had as a general objective to design the interpretation centre of the Afro descendant culture of canton Catamayo province of Loja, so it was necessary to establish three specific objectives: To diagnose the touristic resources for the interpretation centre of the Afro descendant culture of canton Catamayo province of Loja, To develop the proposal of the interpretation centre of the Afro descendant culture of canton Catamayo province of Loja y To constitute the administrative process and to establish promotional strategies for the interpretation centre of the Afro descendant culture of canton Catamayo province of Loja The Methodology used to fulfill the different objectives are the analytical method, that allowed to do a deep analysis of the Afro descendant culture, the inductive method that helped to study the particularities, social and economic incidence, the deductive method that helped to make the corresponding conclusions based on the problems and needs in touristic aspects for the benefit of the culture, and the historical method that allowed to guide the use of historical documents. Similarly, it was used techniques such as the interview and direct observation that permit to gather data and necessary information for the development of the diagnosis. The findings of the research determine through the diagnosis made in the first objective that the canton of Catamayo has a potential tourist offer, just as the Afro descendant culture that has a big amount of cultural manifestations, where were selected the most important ones to develop the proposal of interpretation centre of the culture. Likewise, it was determined the administrative process and the necessary promotional strategies for advertising in different sites and communication means for the interpretation centre. The research concludes that the touristic diagnosis allowed to identify the most important cultural manifestations that has the Afro descendant culture to develop the proposal of the interpretation centre, that are not known in the canton because of the lack of support of relevant authorities, likewise its members lack of touristic knowledge that has been a limiting factor to undertake touristic activities that generate them economic resources, therefore the interpretation centre will allow the community to access to information of the Afro descendant culture, that its members undertake touristic projects improving their quality of life. The recommendations are addressed entirely to the authorities of Municipal GAD of Catamayo canton, to the National Institute of Heritage and Culture, to consider the proposal of the “INTERPRETATION CENTRE OF AFRO DESCENDANT CULTURE”, also that training workshops are conducted to members of the Afro descendant culture, and that they take into account the calendar of annual festivities the celebration of the national day of the afro descendant.